Emergency thoracotomy for massive hemothorax - Aguiar, Eduardo Santiago Ventura de; Ferreira, Alessandra Quaresma; Ferreira, Ida Quaresma; Beier, Suzane Lílian; Borba, Marcelo (Acta Scientiae Veterinariae, 2018)
A tree year old female Cocker Spaniel was admitted, hitted by a car. The patient presented progressive hypotension, epistaxis, fast and weak pulse, capillary refill time (CRT) of 4 seconds and progressive dispnea. An infusion with lactated ringer (90ml/kg/h IV) and oxygen therapy were started. The thoracocentesis revealed massive hemopneumothorax in both sides of the chest, and one thoracic drain was inserted in each hemithorax. Peripherical pulse became untouchable indicating severe blood pressure fall, and the patient got unconscious. In this way, was decided to perform an emergency thoracotomy by a transesternal resection on the fifth intercostal space, and a pulmonary lobectomy was than executed. The patient had a good recovery and at this moment she is healthy.